Art and Beauty in Schelling’s Aesthetics. The Indifference of the Ideal and the Real in «Philosophie der Kunst» - Bosch, Magdalena (Pensamiento. Revista de Investigación e Información Filosófica, 2019)
This article analyzes the idea of art as indifference between the ideal and the real within Philosophy of Art, by Schelling. It is a culminating moment for the work of this author. He concentrates essential concepts already explained in other works like System, Philosophy of nature, Of the I as a principle of Philosophy in it. This analysis discover also other primordial oppositions: between finite and infinite, freedom and nature, the conscious and the unconscious. This opposed terms are each other related within the context of the Ontology of the Absolute, that Schelling described in the mentioned works and it is recollected a more robust version in the 1802-3 text. The present study considers the ideal-real contradiction, its overcoming through the work of art, the relationship of truth and beauty as a representation of the absolute, how art and beauty fulfill this absolute, and the dynamics of the idea spirit penetrating the real nature.
Keywords: Schelling’s aesthetics; Schelling; art; beauty; Philosophie der Kunst